FAKTOR-FAKTOR HUBUNGAN ANTARA KELESTARIAN SOSIAL, EKONOMI, DAN LINGKUNGAN - Laga, Zelvi; Mappellawa, Andi; Sutomo, Andi; Nur, Amal (Universitas Ichsan Sidenreng Rappang, 2025)
Environmental pollution is generally caused by economic activity. Traditional economic theory posits a trade-off between economic growth and environmental quality. However, since the early 1990s, empirical and theoretical literature has grown rapidly. Research has demonstrated the effects of profits on environmental sustainability, including population density control. However, environmental pollution can be controlled to achieve optimal pollution levels that maximize the net benefits of economic activity. Identifying polluters is necessary when determining optimal pollution levels. Economic instruments can be used to pressure polluters to control their economic activities. The selection of economic instruments to be implemented will work best if the value of environmental pollution is known. In fact, pollution is not priceless, and therefore, an economic valuation of pollution is necessary. Several valuation techniques have been introduced, based on the type of pollution. Research shows that conventional policies focus more on pollution control, but this development must be combined with policy choices that focus on eco-efficiency, environmental sustainability, and innovation in the economic development process. Otherwise, economic growth will continue to undermine environmental sustainability in most countries.